Placements through the Lens of Host-Supervisors and Librarianship Students: A Study of Monash University Library Experience. Issue 1 (2nd January 2022) - Dewi, Anita; Velasquez, Diane L.
ABSTRACT: The paper presents students and host-supervisors' perceptions of Monash University Library placement program. The study critically investigates what past placement students perceive as having been gained from the experience and how they see the experience facilitate their future career. In addition, the study also analyses what host-supervisors (library staff members) see as beneficial for placement students, themselves and the library. In this qualitative research, data collection was done through semi-structured individual interviews with participants. The results revealed that students and host-supervisors view placements as a means of putting theory into practice, and highly regard relationship building between placement students and host-supervisors. It was also found that teamwork is one of the host-supervisors' expectations, but none of the students consider teamwork as their expectation. Host-supervisors also perceive the program as beneficial for placement students and the library, but not necessarily for themselves. In addition, students believe that placements facilitate their career planning. Both students and host-supervisors also put forward ideas for placement program improvements.